Effect of phosphorus application on the performance of some cowpea lines - Suzuki, K.; Fatokun, C.; Boukar, O. (Wiley, 2022)
Field experiments were conducted for 2 yr (2014 and 2015) in Fashola, southwestern Nigeria, a low-phosphorus (P) environment (approx. 1 mg kg−1), to determine the effect of P application on nutrient uptake, growth parameters, and yield in four cowpea [Vigna unguiculata (L.) Walp.] genotypes (two low-P tolerant and two low P sensitive). Applications were 0 and 30 kg P ha−1 using single super phosphate broadcast on the soil surface just before planting. Phosphorus is very important for leaf and stem development in cowpea at the vegetative stage (i.e., 5 or 6 wk after seeding). This effect appeared more strongly on the genotype with a high amount of biomass (‘Iron bean’) than on genotypes with low biomass (‘IT97K-499-38’, ‘Sanzi’, and ‘TVu 7778’). However, in all tested genotypes, P application resulted in taller plants, more leaf area, and heavier shoot dry weight. Uptake of P was increased at flowering stage and at the beginning of pod formation, suggesting that P is necessary for pod formation. As proof, the seed weight per pod in both years (with the exception of ‘Iron bean’ in 2015) was significantly higher under P application. An adequate amount of P uptake can lead to high-quality seeds.